PENERAPAN KOMUNIKASI PARTISIPATORY DALAM PENYELENGGARAAN IDXCARBON PADA BEI - Hardjanti, Rani; S. Bekti Istiyanto; Drina Intyaswati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The implementation of carbon trading through the IDXCarbon platform, managed by the Indonesia Stock Exchange (IDX), marks a strategic step in supporting Indonesia’s commitment to reducing carbon emissions. However, the success of this initiative is highly influenced by the communication strategies employed, particularly participatory communication that engages multiple stakeholders. This study aims to analyze how participatory communication is applied by IDX in the development of IDXCarbon and in fostering public and stakeholder engagement. A descriptive qualitative method with a case study approach was used. Data were collected through interviews, observations, and documentation. The findings indicate that IDX has applied participatory communication principles through eight key elements: dialogue, active participation, empowerment, cultural contextualization, access and equity, collectivity, transparency, and feedback. These elements are reflected in various initiatives such as public education programs, newsletters, discussion forums, and the